2021
DOI: 10.1007/s42452-021-04260-w
|View full text |Cite
|
Sign up to set email alerts
|

Influence of slide burnishing process on the surface characteristics of precipitation hardenable steel

Abstract: The surface integrity of the material is the predominant necessity of a component to perform efficiently in varying working conditions. To improve the surface integrity of the workpiece secondary finishing processes are being performed. This work attempts to propose a realistic cryogenic slide burnishing condition for improvement of the surface integrity. The slide burnishing was performed by a novel slide burnishing tool on 17–4 precipitation hardenable stainless steel. The experiment was designed based on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…Surface plot is shown in Figure 4. Both surface characteristics and its roughness were analyzed in steel by using surface plot 26 .Here, the image consists of more peak and valley profiles. It was investigated by employing several parameters and its surface was identified as smooth profile.…”
Section: Surface Topographymentioning
confidence: 99%
“…Surface plot is shown in Figure 4. Both surface characteristics and its roughness were analyzed in steel by using surface plot 26 .Here, the image consists of more peak and valley profiles. It was investigated by employing several parameters and its surface was identified as smooth profile.…”
Section: Surface Topographymentioning
confidence: 99%
“…Surface burnishing can produce a specific texture (up to a depth of several millimetres) and introduce compressive stresses up to approximately -1200 MPa (Przybylski, 1987). The beneficial effects of burnishing treatment include: increasing the hardness of the material, improving fatigue life, increasing resistance to abrasion and surface corrosion (Sachin et al, 2021;Zaleski & Skoczylas, 2019). Burnishing can be used to process internal and external surfaces, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The microhardness of the surface layer after slide burnishing depends on the burnishing speed, feed rate, burnishing force, and the burnishing tip radius [51,52]. In slide burnishing of 17-4 HP stainless steel under the minimum quantity lubrication (MQC) conditions, the maximum surface hardness was obtained by using low burnishing feed and speed yet high burnishing force [53]. Toboła et al [54] found that for Ti6Al4V titanium alloy, the application of slide burnishing and low-temperature gas nitriding increased the surface hardness by 5-10% without compromising the strength of the core material.…”
Section: Introductionmentioning
confidence: 99%
“…Toboła et al [54] found that for Ti6Al4V titanium alloy, the application of slide burnishing and low-temperature gas nitriding increased the surface hardness by 5-10% without compromising the strength of the core material. In the surface layer of slideburnished parts, compressive residual stresses are formed [22,51,53]. The residual stresses induced in the surface layer depend on the tool radius and burnishing force [49], and they are very often moreparallel to the burnishing direction rather than in the perpendicular direction (46-51% higher) [51].…”
Section: Introductionmentioning
confidence: 99%